Pelaksanaan Dakwah Melalui Program Tahsin Tahfidz Metode Ummi di Lembaga Cordova Quran Academy Indonesia - Kurniawan Kurniawan; Siti Shofiyah; Hadiyan Hadiyan; Mahliga Fitriansyah; Sureni Sureni (Hikmah, 2025)
The call to study Islam comes in many forms and ways, especially within Islamic education institutions, which are required to prioritize religious learning over general academic subjects. One of the efforts to revive students’ love for exclusive religious knowledge—particularly the Qur’an—is through structured, systematic, and high-quality da'wah bil hal activities, one of which is the implementation of the Ummi method. This method aims to make the processes of tahsin (Qur’anic recitation improvement) and tahfidz (memorization) easier, more enjoyable, and spiritually meaningful. The purpose of this study is to provide a comprehensive overview of da’wah applications through these Qur’anic programs using the Ummi method, especially in the context of elementary-level education. At this level, the appropriate use of media and methods becomes crucial to shaping students into Qur’ani individuals—those whose character reflects Qur’anic values. Such character formation not only enhances students’ religious capacities but also becomes a valuable provision for navigating life with purpose and moral direction. This research adopts a qualitative descriptive approach with an exploratory inductive analogy model. Ultimately, the study affirms that implementing da’wah with measured and suitable methods can significantly contribute to students’ development—both intellectually and spiritually.